Hydrogel‐Based Janus Micromotors Capped with Functional Nanoparticles for Environmental Applications. Issue 8 (28th May 2020) - Lin, Xinyi; Zhu, Hong; Zhao, Zhe; You, Chunyu; Kong, Ye; Zhao, Yuting; Liu, Jinrun; Chen, Hong; Shi, Xiaojie; Makarov, Denys; Mei, Yongfeng
Abstract: Janus nano/micromotors have been developed into various sizes, shapes, and functions for a blaze of applications especially in biomedical and environmental fields. Here, a fabrication method of Janus micromotors is reported by capping hydrogel microspheres with functional nanoparticles (NPs). Microspheres are prepared in droplet microfluidics relying on hydrogel polymerization to obtain spheres with diameters from 20 to 500 µm. By solidifying a hydrogel layer onto microspheres, functional NPs of MnO2 (catalyst of H2 O2 ), TiO2 (photocatalyst), and Fe3 O4 (magnetic guidance) are adhered onto microspheres resulting in Janus micromotors revealing different functionalities. Dynamics of Janus micromotors (diameter around 250 µm) are explored by analyzing their trajectories in terms of mean squared displacement when immersed in H2 O2 solutions of different concentrations, illuminated by light and guided in an external magnetic field. TiO2 Janus micromotors perform well for water purification tasks as is exemplarily demonstrated with a degradation of Methylene Blue dye in water. The proposed fabrication method is versatile and enables to achieve adjustable coverage of a microsphere with NPs as well as to realize multifunctional Janus micromotors by adhering different NPs (e.g., MnO2 and Fe3 O4 ) on a sphere. This method provides an attractive way to fabricate multifunctional Janus micromotors in a cost‐effective manner for environmental applications. Abstract : A novel strategy is proposed to fabricate Janus micromotors using microfluidics by adhering functional nanoparticles (photocatalytic TiO2, magnetic Fe3 O4, and catalytic MnO2 ) onto microspheres functionalized with a photocurable hydrogel precursor. In addition to the detailed study of the complex dynamics of Janus spheres exposed to different stimuli, their potential in environmental applications is revealed with the focus on water purification.